Redefining the Standards in Attic, Koine, and Atticism - Bozia, Eleni,; Machado, Robert,; Monaco, Chiara, (Classical Studies E-Books Online, Collection 2024., 2024)
Scholarship surrounding the standard varieties of Ancient Greek (Attic, the Koine, and Atticistic Greek) focused from its beginnings until relatively recently on determining fixed uniformities or differences between them. This collection of essays advocates for understanding them as interconnected and continuously evolving and suggests viewing them as living organisms shaped by their speakers and texts. The authors propose approaches that integrate linguistics, sociolinguistics, and literary studies to explore how speakers navigate linguistic norms and social dynamics, leading to innovations and reshaping of standards. Each contribution challenges the dichotomy between standards and deviations, suggesting that studying linguistic diversity through socio-literary interconnectedness can enrich our understanding of language history and cultural wealth.